Tau Protein and Its Role in Blood–Brain Barrier Dysfunction - Michalicova, Alena; Majerova, Petra; Kovac, Andrej (Frontiers in Molecular Neuroscience, 2020)
The blood-brain barrier plays a crucial role in maintaining the specialized microenvironment of the central nervous system. In aging, there is a decline in the stability of the blood-brain barrier leading to increased permeability. The list of central nervous system pathologies involving blood-brain barrier dysfunction is growing. The opening of the blood-brain barrier and subsequent infiltration of serum components to the brain can lead to a host of processes resulting in progressive synaptic, neuronal dysfunction, and detrimental neuroinflammatory changes. Such processes have been implicated in different diseases, including vascular dementia, stroke, Alzheimer´s disease, Parkinson´s disease, multiple sclerosis, amyotrophic lateral sclerosis, hypoxia, ischemia and diabetes mellitus. The blood-brain barrier damage is also observed in tauopathies that lack Aß over-production, suggesting a role for tau in blood-brain barrier damage. Tauopathies represent a heterogeneous group of around twenty different neurodegenerative diseases characterized by abnormal deposition of the microtubule-associated protein tau in cells of the nervous system. Neuropathology of tauopathies is defined as intracellular accumulation of neurofibrillary tangles consisting of aggregated hyper- and abnormal phosphorylation of tau protein and neuroinflammation. Chronic neuroinflammation in tauopathies is driven by glial cells that potentially trigger the disruption of the blood-brain barrier. Pro-inflammatory signaling molecules such as cytokines, chemokines and adhesion molecules produced by glial cells, neurons and endothelial cells, in general, cooperate to determine the integrity of the blood-brain barrier by influencing vascular permeability, enhancing the migration of immune cells and altering transport systems. The inflammatory processes promote structural changes in capillaries such as fragmentation, thickening, atrophy of pericytes, accumulation of laminin in the basement membrane and increased permeability of blood vessels to plasma proteins. Here we summarize the knowledge about the role of tau protein in blood-brain barrier structural and functional changes.